Methodology Development of Interactive E- Courses - Sodiqovich, Usmonov Murod; Burxonovich, Abdullayev Xolxuja; Mamarasulovich, Suvonqulov Baxtiyor (Universitas Muhammadiyah Sidoarjo, 2018)
This article describes the goals and objectives of creating interactive e-learning courses based on multimedia technologies and develops a methodology for their use in the educational process.